Design of Batik Motif Detection System Using Deep Learning Method - Janinda Puspita Anidya; Hindriyanto Dwi Purnomo (International Journal of Information Technology and Business, 2025)
Batik in Indonesia is growing very rapidly, almost every region or city in Indonesia has a variety of batik motifs. The batik motifs owned by each region are their own wealth and heritage in each region that must be preserved and maintained properly. So the Indonesian people need to collaborate with each other to place batik preservation as a top priority in the field of preserving the nation's culture. Because knowledge of batik motifs in Indonesia is important in order to maintain the culture of the Indonesian nation, including knowledge of batik motifs in each of their respective regions, so there is a need to make it easier for humans to recognize batik motifs in regions in Indonesia quickly and easily. This study aims to build a system model that can assist humans in recognizing batik motifs in Indonesia through this batik motif detection system. This research produces a model that can detect batik motifs from every area in Central Java. The conclusion of this study is a batik detection model that can help and introduce to the public about various batik motifs from each region.Batik in Indonesia is growing very rapidly, almost every region or city in Indonesia has a variety of batik motifs. The batik motifs owned by each region are their own wealth and heritage in each region that must be preserved and maintained properly. So the Indonesian people need to collaborate with each other to place batik preservation as a top priority in the field of preserving the nation's culture. Because knowledge of batik motifs in Indonesia is important in order to maintain the culture of the Indonesian nation, including knowledge of batik motifs in each of their respective regions, so there is a need to make it easier for humans to recognize batik motifs in regions in Indonesia quickly and easily. This study aims to build a system model that can assist humans in recognizing batik motifs in Indonesia through this batik motif detection system. This research produces a model that can detect batik motifs from every area in Central Java. The conclusion of this study is a batik detection model that can help and introduce to the public about various batik motifs from each region.